Ecological Connectivity of Plant Communities for Red Blotch Disease Dynamics Revealed by the Dietary Profiles and Landscape-Level Movement of Spissistilus festinus - Victoria Hoyle; Heather Headrick; W. Rodney Cooper; Hannah G. Fendell-Hummel; Monica L. Cooper; Madison Flasco; Elizabeth Cieniewicz; Michelle Heck; Marc Fuchs (Phytobiomes Journal)
The epidemiological relationship between arthropod dispersal and plant communities is poorly understood at the landscape level. We investigated the connectivity of natural and cultivated plants in vineyard ecosystems for red blotch disease dynamics by characterizing the dietary history of Spissistilus festinus, a treehopper vector of grapevine red blotch virus. Molecular analysis of the gut content of 205 S. festinus caught in 71 vineyard sites and the flora proximal to vineyards in Napa Valley, California, revealed a total of 171 genera from 60 plant families with a preeminence of Asteraceae, Fabaceae, and Vitaceae over two growing seasons, illustrating dietary profiles composed primarily of natural vegetation. An indicator species analysis identified the strength of ecological associations by showing distinct seasonal feeding trends related to weather patterns and host repertoires unique to some vineyard sites with estimated S. festinus travel distances of up to 2 km. Potential reproductive and overwintering hosts of S. festinus were identified in natural habitats, and an ecological relatedness between free-living vines in riparian corridors and vineyards for grapevine red blotch virus transmission was documented. Together, our findings on landscape vegetation connectivity and S. festinus dispersal transformed our understanding of red blotch disease ecology and informed disease management options. [Figure: see text] Copyright © 2025 The Author(s). This is an open access article distributed under the CC BY-NC-ND 4.0 International license.